(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The increasing risk of climate change is making changes to all aspects of humanity, including the financial sector. This study aims to determine the spillover effect between oil commodities, green stock markets in Indonesia and America and Bitcoin. Using the Vector Autoregression method, this study divides into several time periods, namely the overall period (April 2016 - February 2023), the period before the COVID-19 pandemic (April 2016 - December 2019), the period after the COVID-19 pandemic (January 2020 - February 2022), the Russian-Ukrainian war period (February 2022 - February 2023) and uses daily return data from Crued Oil WTI, Nasdaq OMX Green Economy, SRI-KEHATI Index and Bitcoin. The results showed that in the crisis period there was a spillover effect on all research variables. Therefore, investors should avoid these four instruments when there is a shock to one of the financial instruments. That way, investors can reduce the loss of their investment and wait for the opportunity to buy back financial assets after the crisis period is over.